2020
DOI: 10.3390/polym12061326
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of pH Sensitive Chitosan/3-Glycidyloxypropyl Trimethoxysilane (GPTMS) Hydrogels by Sol-Gel Method

Abstract: pH responsive chitosan and 3-Glycidyloxypropyl trimethoxysilane (GPTMS) hydrogels were synthesized by the sol-gel crosslinking reaction. GPTMS was introduced to influence several behaviors of the chitosan hydrogels, such as the swelling ratio, mechanical properties, swelling thermodynamics, kinetics, and expansion mechanism. The functional groups of Chitosan/GPTMS hybrid hydrogels were verified by FT-IR spectrometer. Differential scanning calorimetry (DSC) and the thermogravimetric analysis (TGA) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In contrast, systems that maintained acidic pH showed a great dependence of both moduli on the frequency and, as can be observed, G″ values were higher than those obtained for G′, which means that these systems were concentrated solutions, instead of hydrogels, since they did not show a solid character. This was already predicted by Li et al (2020), which indicates that acidic pH values generate certain stability in cationic hydrogels, being favored at higher pH values, since these groups are protonated, reinforcing the structure [ 24 ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, systems that maintained acidic pH showed a great dependence of both moduli on the frequency and, as can be observed, G″ values were higher than those obtained for G′, which means that these systems were concentrated solutions, instead of hydrogels, since they did not show a solid character. This was already predicted by Li et al (2020), which indicates that acidic pH values generate certain stability in cationic hydrogels, being favored at higher pH values, since these groups are protonated, reinforcing the structure [ 24 ].…”
Section: Resultsmentioning
confidence: 53%
“…Regarding gelling, the pH change favors physical interactions, such as electrostatic interactions, hydrogen bonding, hydrophobic interactions as well as multi-physical ones [ 23 ]. Furthermore, the change from acidic to neutral pH value also generates protonation of amino groups, improving the strength of the formed hydrogel by electrostatic repulsions [ 24 ]. Lastly, as NaOH is incorporated superficially, gelation time and temperature are also two key aspects to take into account when evaluating pH diffusion and heterogeneity of the systems.…”
Section: Methodsmentioning
confidence: 99%
“…All the experiments were done in triplicate to ensure reproducibility. As a general rule, it was observed that increasing the concentration of GPTMS decreases the swelling capacity [ 57 ] thus the aerogels presented total absorbed mass ratios ranging between 3.75 and 1.75 for CS7G2 and CS10G4, respectively. It is worth to note that these two samples were mechanically stable in the swollen state, exhibiting characteristic of class II hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 b represents the swelling capacity versus CS content for different GPTMS/CS molar ratios and confirmed the influence of GPTMS on the swelling capacity, with G4 aerogel series (samples CS8, CS9 and CS10) showing more regular and lowest total absorption values (1.85–2.04). This was explained by the fact that increasing GPTMS made pore size to decreased (see Table 2 ) and the aerogel became more compact and highly crosslinked, which hinders swelling [ 32 , 57 ]. Summarizing, the affinity of the hybrid chains of the porous aerogels to the aqueous PBS, together with the swelling phenomenon observed in the hybrid structure, would be responsible for these high values of the absorption capacity obtained.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the porosity of Gel/PVA hydrogel discs, each disc was measured before immersion in absolute ethanol for 24 h. Each disc was then removed, and the excess ethanol wiped off with tissue paper to measure the weight. The porosity percentage was determined using the following Equation (7) [ 38 ]: where “M 2 ” represents the mass of the disc after removal from the ethanol solvent, “M 1 ” represents the mass of the disc before immersion in the ethanol solvent, “ρ” represents the density of the absolute ethanol and “V” represents the volume of the hydrogel disc.…”
Section: Methodsmentioning
confidence: 99%